FROM TRANSACTIONAL TO TRANSFORMATIONAL: MEASURING THE ROI OF STRATEGIC HR ANALYTICS IN TALENT DECISION-MAKING - Ira Maylita; Ramon Zamora; Oktavianti (RADJA PUBLIKA, 2026)
This study explores the transformation of the Human Resource (HR) function from a transactional role to a strategic partner through the adoption of strategic HR analytics. Using a mixed-methods approach, the research combines quantitative HR metrics with qualitative insights from HR professionals to evaluate the impact of analytics on talent decision-making. The findings reveal that organizations utilizing advanced HR analytics achieve improved outcomes in employee retention, quality of hire, workforce productivity, and engagement. The study also identifies a positive relationship between analytics maturity and organizational performance. Furthermore, it distinguishes between direct ROI, such as cost savings in recruitment and turnover, and indirect ROI, including enhanced decision-making and cultural alignment. Despite these benefits, challenges such as data quality issues and limited analytical capabilities remain. The study concludes that strategic HR analytics is essential for driving evidence-based management and achieving sustainable competitive advantage in modern organizations.